Geographic structure and dynamics in mountain plover - Wunder, Michael B., author; Noon, Barry R., advisor; Ben-David, Merav, committee member; Knopf, Fritz, committee member; Webb, Colleen, committee member (Colorado State University. Libraries, 2007)
The mountain plover population is thought to have declined by sixty percent over the past 30 years. Most mountain plovers spend the winter in a highly agricultural landscape in Imperial County, California where the habitat dynamics are completely determined by human policy. To better understand potential impacts of land use decisions in Imperial County, I studied range-wide spatio-temporal links in the demography of mountain plover. I used color bands and stable isotope concentrations in feathers to describe the provenance of plovers wintering in California. Because the use of stable isotopes for this purpose is relatively new, the efficacy of the tool is not well understood. I used feathers of known origin to study some fundamental assumptions of the approach and proceeded to derive a modeling framework to better reflect the state of knowledge about stable isotope ecology. The geographic resolution associated with assigning an individual to a location is relatively coarse, but informative. My work is presented in four chapters, each intended as a stand-alone contribution. Chapter one tests the use of stable isotopes for studying the breeding provenance of wintering mountain plovers based on methods described in the literature. The inferential and sampling frameworks in the literature were inconsistent and I suggest a discrete assignment test framework instead. Chapter two investigates the influence of known sources of error on the certainty of geographic assignments with the approach described in chapter one. Chapter three departs from the assignment test approach and presents a way to directly model sampling effects over a known process based on the physical chemistry of stable hydrogen isotopes in precipitation. I use this model to build and explore probability surfaces that describe the probability of origin for birds from stable hydrogen isotopes in feathers. Chapter four tests the use of these probability surfaces using recaptured plovers and illustrates the application of these surfaces to the problem of mountain plover provenance. In this last chapter, I present evidence for climate-related shifts in geographic provenance of recruitment into the population of mountain plovers.
Keywords: ecology